Desenvolvimento de um medidor de fase para um sistema de biotelemetria passiva - Bertotti, Fábio Luiz (2005)
This work describes the development of a phase measurement equipment for use in a passive biotelemetric system, whose system and measurement technique were developed before in the Biotelemetry Laboratory of the UTFPR. Based on a new technique and phase measurement system developed in this work it was possible to implement an equipment to measure the input phase impedance of the conceived biotelemetric system. A new calibration method and its respective system are described, which has shown to be efficient and provided the aimed linearity response of the corresponding intracorporeal temperature. The experiments have shown that the equipment and the biotelemetric system resulted in temperature measurements, for the range from 30 to 45ºC, with errors down to ± 2% and with resolution of 0,1 degree in temperature, considering that the distance between the interrogator and implantable coil was 10 mm, whereas the maximum distance was 16 mm. The repeatability of 50 measurements accomplished by the equipment was calculated, resulting in errors below ± 3% referred to its mean.